Postsurgical Depressive Symptoms and Proinflammatory Cytokine Elevations in Women Undergoing Primary Treatment for Breast Cancer. Issue 1 (January 2016) - Bouchard, Laura C.; Antoni, Michael H.; Blomberg, Bonnie B.; Stagl, Jamie M.; Gudenkauf, Lisa M.; Jutagir, Devika R.; Diaz, Alain; Lechner, Suzanne; Glück, Stefan; Derhagopian, Robert P.; Carver, Charles S.
ABSTRACT: Objective: Depression and inflammation may independently promote breast cancer (BCa) disease progression and poorer clinical outcomes. Depression has been associated with increased levels of inflammatory markers in medically healthy individuals and patients with cancer. However, inconsistencies in study time frames complicate interpretation of results within specific cancer types. This study examined relationships between depressive symptoms and inflammation in women with early-stage BCa before beginning adjuvant treatment. Methods: Women with Stage 0-III BCa were recruited approximately 4 to 8 weeks after surgery. Depressive symptoms were assessed using the Hamilton Rating Scale for Depression, and blood samples were collected to quantify circulating levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor α (TNF-α) by enzyme-linked immunosorbent assay. Analyses of covariance were used to test for group differences (elevated versus low depressive symptoms) in levels of cytokines. Multiple regression analyses were used to examine relationships between continuous severity of depressive symptoms and levels of cytokines adjusting for relevant biobehavioral covariates. Results: Thirty-six (40%) of 89 patients showed elevated levels of depressive symptoms and, in adjusted models, had marginally higher levels of IL-1β (mean [M] = 14.49 [95% confidence interval CI = 6.11–32.65] versus M = 4.68 [95% CI = 1.96–9.86] and IL-6 [M = 88.74 {95% CI = 33.28–233.96} versus M = 61.52 {95% CI = 27.44–136.40}]) significantly higher levels of TNF-α (M = 17.07 [95% CI = 8.27–34.32] versus M = 6.94 [95% CI = 3.58–12.80]) than did women with low depressive symptoms. Across the spectrum of depressive symptoms, greater magnitude of depressive symptoms was related to greater levels of IL-1β ( β = 0.06, p = .006, R 2 = 0.25) and TNF-α ( β = 0.06, p = .003, R 2 = 0.27). Conclusions: Postsurgery and preadjuvant treatment for early-stage BCa, depressive symptoms covary with elevated levels of multiple proinflammatory cytokines. Findings have implications for psychosocial and biological interventions concurrently focusing on depression and inflammation. Trial Registration: NCT01422551.